Informed consent in dental radiology: a pending matter - Leslie Romina Paredes Cruz; Maria Eugenia Guerrero Acevedo (Editorial Ciencias Médicas, 2022)
Introduction: In the dental field, the use of intraoral, extraoral and even volumetric computed tomography is very common. Intraoral X-rays have a low dose of radiation compared to volumetric CT scans that can emit a higher dose of radiation with some degree of risk to patients. Although the importance of the use of informed consent and the risks during these procedures are known, very little has been reported about the use of informed consent in oral and maxillofacial radiology. Objective: Analyze the benefits and challenges of using informed consent in dental radiology. Main Comments: Currently, there is no clear consensus in the dental community on whether the patient's informed consent should be obtained before they undergo an imaging examination with ionizing radiation. Its application repetitively or prolongedly could affect the patient in the long term. Global considerations: There is a universal consensus to highlight the importance of informed consent in the entire field of health. However, in practice, its realization can lead to certain difficulties, such as the identification of the person responsible for its implementation, the time it takes to execute it and the concern to cause unnecessary fear in the patient. If these difficulties can be overcome, we can see the benefits of having a clear consensus for the use of informed consent in the dental area.